Industry 4.0 in Small and Medium-Sized Enterprises (SMEs) : Opportunities, Challenges, and Solutions. - Kotecha, Ketan; Kumar, Satish; Bongale, Arunkumar; Suresh, R. (CRC Press, 2022)
Focusing on the broader areas of Industry 4.0 as it applies to small and medium-sized enterprises (SMEs), this book offers a smooth adoption of techniques and technologies and presents advances, challenges, and opportunities for implementation. It will also enhance the role of academia by training new engineers on Industry 4.0 and digital transformation. Industry 4.0 in Small and Medium-Sized Enterprises (SMEs): Opportunities, Challenges, and Solutions presents concepts of predictive maintenance, digital factory, digital twin, additive manufacturing, and machining for sustainable development. It discusses the challenges faced by adopting Industry 4.0 including new security and privacy measures in the whole smart manufacturing setup while also explaining the impact of Industry 4.0 on Lean production systems. Implementation recommendations in the form of case studies, research studies, and the role academia can play are also provided. Practitioners, research scholars, academicians, and those studying or working in the Industry 4.0 sector will find this book of interest.